Gelauweerde Beelden. - De Smedt, Raf; Ilegems, Paul; Theys, Hans; Vanhemelryck, F.; Eyskens, Peter; Van Eeckhaute, Arsène; Sint Jorispand, Antwerpen (Antwerpen : Koninklijke Academie voor Schone Kunsten Antwerpen, 2004)
Wright, Cindy ; Claerbout, Mark ; Andrews, Nick ; Cornelis, Ann ; Corluy, Eva ; Jacques, Filip ; Liekens, Tom ; Ooms, David ; Maas, Lieve ; Robeyns, Philippe ; Pannekoucke, Orphee ; et al.
Sint-Jorispand van het Elzenveld, Antwerpen, 13 november tot 19 december 2004
kunstcatalogus
Keywords: Vlaanderen